2013
DOI: 10.1017/s1368980013002000
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of dietary fibre intake on glycosylated haemoglobin A1c level and glycaemic control status among Chinese patients with type 2 diabetes mellitus

Abstract: Objective: Dietary fibre has been linked to lower levels of glycosylated haemoglobin A1c (HbA1c) among diabetes patients. The present study aimed to evaluate the long-term effect of dietary fibre on HbA1c levels among Chinese patients with type 2 diabetes mellitus. Design: Two cross-sectional surveys were conducted in 2006 and 2011, with the second one being a repeat survey on a sub-sample from the initial one. In both surveys, an in-person interview was conducted to collect information on demographic characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
9
1
1
Order By: Relevance
“…In the present study using the QR method, we observed significant associations of both insoluble dietary fibre intake and GI value with HbA 1c levels, especially among patients who did not have their blood glucose under control. Unlike the parametric logistic regression method used in our previous study ( 12 ) in which an average association was estimated among all participants without considering whether the size of the association was dependent on the level of blood glucose control, the non-parametric QR approach adopted in the present study allowed us to identify differing regression coefficients across the conditional distribution of HbA 1c and provided a more complete picture of how the dietary factors and HbA 1c levels are associated ( 14 ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study using the QR method, we observed significant associations of both insoluble dietary fibre intake and GI value with HbA 1c levels, especially among patients who did not have their blood glucose under control. Unlike the parametric logistic regression method used in our previous study ( 12 ) in which an average association was estimated among all participants without considering whether the size of the association was dependent on the level of blood glucose control, the non-parametric QR approach adopted in the present study allowed us to identify differing regression coefficients across the conditional distribution of HbA 1c and provided a more complete picture of how the dietary factors and HbA 1c levels are associated ( 14 ) .…”
Section: Discussionmentioning
confidence: 99%
“…As described in our previous study ( 12 ) , 979 prevalent patients with type 2 diabetes were recruited from the communities of Pudong New Area of Shanghai, China, and were interviewed from October to December 2006. They were followed up from May to July 2011 using a similar protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased fiber in the diet is associated with a reduction of glycated hemoglobin (HbA1c), improved lipid profile, and loss of body weight in type 2 diabetes patients. It has been proposed that appropriate consumption of fruit in the diet may be an adequate strategy to reduce HbA1c, given the fiber content, and prevent complications from diabetes [ 1 , 2 ]. Several clinical trials have documented a positive effect of dietary fiber, [ 3 ] and in cross-sectional studies this effect has also been observed in different Asian populations [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generalising from these observations, no two studies examining the same issue from within or among laboratories can be assumed alike, and no two participants examined within a study can be assumed alike even when categorised similarly for clinical purposes. Such heterogeneity within and among studies is common, and failure to account for it can lead to results with an imprecise estimate of effects or associations, and failure to find truer probabilities or even any effect or association at all, as colleagues of Tan et al report in an earlier publication ( 9 ) .…”
mentioning
confidence: 99%